KAJIAN STRATEGI KEBIJAKAN INDUSTRI OLAHAN KARET RIBBED SMOKED SHEET (RSS) BERBAHAN BAKU LATEKS KEBUN DALAM UPAYA PENINGKATAN MUTU PRODUK - Garli Marsantia; Erdi Suroso; Tanto Pratondo Utomo (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2014)
Natural rubber processing demand has increased every year because of the demand from tire industries and other rubber based industries. The problem of RSS industries with raw material of field latex was low quality of final products. The purposes of this study were to identify factors that affected quality of RSS (Ribbed Smoked Sheet) product and to construct strategies to improve the quality of RSS (Ribbed smoked sheet) products. Data were collected in two ways, there were primary data and secondary data. Data were analyzed using SWOT method and continued using qualitative (descriptive) method. Weighting results showed for internal factors had strength value of 2,879, and weaknesses value of 2,705 then the difference value +0.174. While the weighting for external factors had opportunities value of 2,410, and threats value was 1.306. then the difference value was +1,433 . The conclusion that could be drawn from this research is that The quality of RSS product can be improved by strictly implementing the standard operating procedure , developing human resource abilities, collaborating research with other institutions , implementing and monitoring the use of SNI 06-2047-2002 for latex raw materials. Keywords : Ribbed Smoked Sheet, SWOT